Removing barriers to developing green credit at Vietnamese commercial banks - Phan, Thị Cúc; Do , Đoan Trang; Ngo , Thị Phương Dung (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Green Credit is one of the tools; Green Finance has developed in many countries around the world, since the early years of this decade of the 20th century, many studies on Green Credit have appeared, of which the pioneering Green Credit researchers are typical. In Vietnam, on October 1, 2021, the Prime Minister issued Decision No. 1658/QD-TTg approving the national strategy on green growth for the period 2021-2030, vision 2050 with the goal of green growth contributing to promoting economic restructuring associated with growth model innovation, aiming to achieve sustainable economic prosperity, environmental justice and society, towards a green, carbon-neutral economy and contributing to the goal of limiting global temperature increase. The World Bank’s National Climate and Development Report for Vietnam estimates that Vietnam needs to invest an additional 368 billion USD by 2040, equivalent to 6.8% of GDP/year to adapt to climate change and Green growth - this is the biggest difficulty of Vietnam in terms of capital. The authors reviewed the development of Green Credit in Vietnam in the period of 2020-2023 and focused on finding bottlenecks and barriers to propose solutions to contribute to the development of Green Credit towards implementing the Prime Minister’s national strategy on green growth to 2030 and vision to 2050 with qualitative research methods and data collected by the authors of the article, analyzed and synthesized from data of reputable commercial banking organizations that have been notified by the State Bank of Vietnam. The authors delved into this article with the aim of contributing to removing some barriers to Green Credit development, paving the way for the development of Green Credit in Vietnam.